The Missing Fisher Effect on Nominal Interest Rates in the 1950s - Wilcox, James A. (The Review of Economics and Statistics, 1983)
The response of nominal interest rates to price increases has been intensively studied since the onset of substantial inflation and historically high interest rates in the late 1960s. Early empirical investigations (Yohe and Karnosky (1969), Gibson (1972), and Pyle (1972)) tested the Fisher hypothesis that nominal rates react one-for-one to changes in the expected inflation rate. Paralleling results in the wage-price literature, these studies often found that nominal rates appeared to adjust too little to imply neutrality with respect to expected inflation. Theoretical work by Mundell (1963) and Tobin (1965) that incorporated wealth effects, by Sargent (1972) that considered an extended macromodel, and by Darby (1975) and Feldstein (1976) that allowed for income tax effects, however, suggested that additional variables, like measures of fiscal and monetary policy, may be relevant and that nominal rates may change by either more or less than unity in response to a one unit change in expected inflation. Two puzzling features of the response of nominal rates to expected inflation remain. First, even when other factors are included, estimates of that response are unstable for the postwar period (see Cargill and Meyer (1977)). Second, empirical studies to date have failed to produce any statistically discernible impact of expected inflation on interest rates during the 1950s (see Cargill and Meyer (1974) and Cargill (1976)). Similarly striking is the sizeable residual autocorrelation exhibited by nearly all estimates that include the 1950s. These symptoms of model misspecification imply that an important factor may have been omitted from previous models. A reduced form model of nominal interest rates that allows for an additional impact, that of factor supply shocks, is advanced in section II. The empirical tests in section III show that, once this variable is included, a significant relation between interest rates and expected inflation emerges for the 1950s. We also show that our specification is stable over the entire post-Accord period. Section IV concludes.